Some of the kinematic variables and their relationship to the accuracy of the dimensional rear blow with the badminton for players ages (13-15) - Zighair, Dr. Raid Mhawes (International Journal of Psychosocial Rehabilitation, 2020)
Through the presence of the researcher that in the field of badminton as well as through observation for most young players found and that there is weakness in the precision strike dimensional background they need a high degree of focus and direction of the feather in the farthest place is to the area back to the stadium rival, and this causes To not achieving positive results due to poor investment of the kinematic variables, which is one of the factors that help in the success of the performance of this skill.